Identification and significance of 3ß-alkyl steranes in the Eogene lacustrine sediments and petroleum of China - Wang, Guangli; Zhang, L.; Wang, T. (Science in China Press/Zhongguo Kexue Zazhishe, 2006)
Several homologous series of steranes with alkyl side chains (C1 to C4) at the 3ß position have been identified in the Jiyang Eogene lacustrine deposition. It is postulated that its precursors repre-sent a new class of steroids, alkylated at the C-3 po-sition with a polyhydroxy n-alkane. These precursors may have been formed by the bacterial addition of a ribose sugar to ?2-sterenes, diagenetic alteration products of steroids synthesized by eukaryotes. 3-alkyl steroids might substitute for hopanols in bac-terial membranes. When they are present in a sam-ple, the patterns of the isomer distributions of 3-alkyl steranes are similar to desmethyl steranes except for lower rearranged ones. It is shown that the configu-rational isomerization of 3-alkyl steranes is trending in line with that of desmethyl steranes with increasing of maturity. The abundance of 3-alkyl steranes may be controlled by the depositional environments; they are primary in saline or near shore lacustrine, mod-erate in shallow lacustrine, poor in sub-deep to deep lacustrine relative to the 4-methyl steranes.